2020
DOI: 10.37335/ijek.v8i2.115
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Legal Risk and Its Impact on the Business of Smes

Abstract: One of the prerequisites for a favourable business environment is a stable legislative context and law enforcement. In particular, for SMEs, that do not have the financial resources for stable legal assistance, legal risk is becoming one of the most important business risks. The aim of this paper is to enrich the current scientific knowledge with a comparison of the impact of legal risk on SMEs in selected countries. The empirical research was conducted by Tomas Bata University in Zlín during 2019-2020. In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The immense contributions of Small and Medium Enterprises (SMEs) in the entire world cannot be underestimated (Sanjo & Ibrahim, 2017;Jibril, Kwarteng, & Chovancova, 2019). SMEs are well known for contributing about 40% to Gross Domestic Product (GDP) and 70% creation of employment opportunities (Qalati et al, 2021;Chatterjee & Kumar 2020;Virglerova et al, 2020;Ye & Kulathunga, 2019;Belas et al, 2020;Kiram & Saputra 2021). SMEs, therefore, play a major role in the growth and development of both developed and developing countries (Pandya 2012;Lazányi, & Amoah, 2020).…”
Section: Introduction International Journal Of Entrepreneurial Knowledgementioning
confidence: 99%
“…The immense contributions of Small and Medium Enterprises (SMEs) in the entire world cannot be underestimated (Sanjo & Ibrahim, 2017;Jibril, Kwarteng, & Chovancova, 2019). SMEs are well known for contributing about 40% to Gross Domestic Product (GDP) and 70% creation of employment opportunities (Qalati et al, 2021;Chatterjee & Kumar 2020;Virglerova et al, 2020;Ye & Kulathunga, 2019;Belas et al, 2020;Kiram & Saputra 2021). SMEs, therefore, play a major role in the growth and development of both developed and developing countries (Pandya 2012;Lazányi, & Amoah, 2020).…”
Section: Introduction International Journal Of Entrepreneurial Knowledgementioning
confidence: 99%
“…It is also important to understand the link between aspects of the business sector and the business environment (Khan et al, 2019). The market, economic and financial risks are the most important risks (Virglerova et al, 2020), which determine the quality and performance of enterprises (Dvorsky et al, 2019). He et al (2017) examines the linkage of dividend policy and earnings management and the fact if the mutual bonds between countries changes due to divergent institutional strength or transparency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Legal risk is defined as the result of losses suffered to a particular business due to its disregard for business laws (Virglerova, Conte, Amoah, & Massaro, 2020). Even though the legal environment resulted not being a significant factor in predicting business risk (Çera et al, 2019), it is considered an equally positive factor that influences future business perception (Dvorsky et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though the legal environment resulted not being a significant factor in predicting business risk (Çera et al, 2019), it is considered an equally positive factor that influences future business perception (Dvorsky et al, 2020). Furthermore, Virglerova et al (2020) concluded that entrepreneurs have a positive attitude when the legal environment is not overregulated, does not harm the future of the business.…”
Section: Literature Reviewmentioning
confidence: 99%